Resources potential for the development of enogastronomic tourism in Ukraine - Мотузенко, Олена Олександрівна; Бульба, Вікторія Валеріївна; Джанколла, Дарина Вадимівна (Київський національний університет імені Тараса Шевченка, 2020)
The purpose of the study is to clarify the issues of theoretical and methodological substantiation of the resource potential of enogastronomic tourism and to develop recommendations for its optimization. Method. Based on general scientific methods of analysis and synthesis of information from scientific sources and official sources of leading organizations involved in the development of Gastronomic heritage and enogastronomic tourism, the method of logical structures and interpolation of the results of the analysis of best practices, the following results were achieved: the substantive essence of the concepts “Gastronomic and Enological heritage”, “traditional food and cuisine” and their role in the development of enogastronomic tourism are revealed; presented best practices for promoting enogastronomic heritage with the tools of enogastronomic tourist routes - Wine and Taste Roads and Festivals; the resource potential of enogastronomic tourism in Ukraine is analyzed. Scientific novelty. The substantive essence of the resource potential of enogastronomic tourism is highlighted, a graphical model of its structural organization is developed. Practical importance. We propose a system of actions, the implementation of which will increase the resource potential of enogastronomic tourism in Ukraine, by creating additional value of traditional food and beverages to turn them into objects of tourist attraction.

Метою дослідження є висвітлення питань теоретико-методологічного обґрунтування ресурсного потенціалу еногастрономічного туризму та розробка рекомендацій щодо його оптимізації. Методика. На основі загальнонаукових методів аналізу та синтезу інформації з наукових джерел та офіційних джерел провідних організацій дотичних до розвитку Гастрономічної спадщини та еногастрономічного туризму, методу логічних структур та інтерполяції результатів аналізу кращих практик, досягнуто наступні результати: розкрито змістовну суть понять “Гастрономічна та Енологічна спадщина ”, «традиційні харчові продукти та кухня» та їх роль у розвитку еногастрономічного туризму; презентовано кращі практики просування еногастрономічної спадщини інструментами еногастрономічних туристичних маршрутів – Доріг вина та смаку та фестивалів; проаналізовано ресурсний потенціал еногастрономічного туризму в Україні. Наукова новизна. Висвітлено змістовну суть ресурсного потенціалу еногастрономічного туризму, розроблено графічну модель його структурної організації. Практична значимость. Запропоновано систему дій, реалізація яких дозволить підвищити ресурсний потенціал еногастрономічного туризму в Україні, шляхом створення додаткової вартості традиційних харчових продуктів та напоїв для перетворення їх в об’єкти туристичного тяжіння.
Ресурсний потенціал розвитку еногастрономічного туризму в Україні
Keywords: традиційний харчовий продукт; еногастрономічна спадщина; енологічна спадщина; енологічний туристичний потенціал; еногастрономічний туризм; національна кухня; ресурсний потенціал; traditional food; enogastronomic heritage; enological heritage; enological tourism potential; enogastronomic tourism; national cuisine; resource potential